Konseling Cognitive Behavior Therapy dalam Mereduksi Prokrastinasi Menyelesaikan Skripsi - Ramtia Darma Putri; Erfan Ramadhani; Palasara Brahmani Laras; Kadek Suhardita (Universitas PGRI Palembang, 2023)
The delay in completing the thesis begins with the student's mindset that affects the actions taken in completing their responsibilities in working on the thesis. Students should be able to do something that is not useful, on the contrary, postpone doing the thesis by doing fun activities. The delay in completing the thesis is often known as procrastination in completing the thesis. This delay can be given intervention counseling services using the Cognitive Behavior Therapy (CBT) approach. The purpose of writing this article is to see the extent to which the use of the Cognitive Behavior Therapy (CBT) approach in overcoming the problem of student thesis completion. The research method used in writing this article uses a literature review that utilizes 9 relevant research results. Based on the literature that has been carried out, the conclusion in this article is the effectiveness of the Cognitive Behavior Therapy (CBT) counseling approach in overcoming various cognitive problems that affect behavior, especially in procrastinating students' thesis completion.